Some Important Topics of Maktubat-i-Sadi and Their Philosophico-Spiritual Significance (Philosophy and Progress, 2023)
Hazrat Sharafuddin bin Yahyah Maneri was a scholar and Sufi of the thirteenth-fourteenth centuries. He was a prolific writer. One of his important books is a collection of letters titled Maktubat-i-Sadi. The article focuses to bring out the main themes of the book and identified ten topics to discussed. They are: 1. Concept and love of God; 2. Deceiving nature of the world; 3. Sin and repentance; 4. Necessity of a qualified spiritual guide and obedience to his guidance; 5. Origin and need of Sufism; 6. Poverty and its role in the purification of evil soul; 7. Rendering selfless service to others; 8. Fate and predestination; 9. Observance of the Shariah; and 10. Acquisition of good qualities and shunning of the evil ones. The philosophical and spiritual significance of these teachings have been pointed out in this article.Philosophy and Progress, Vol#71-72; No#1-2; Jan-Dec 2022 P 79-96